2016
DOI: 10.1111/1744-7917.12374
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal behavior of yellowjacket (Vespula germanica) queens

Abstract: Understanding the factors that affect animal dispersal behavior is important from both fundamental and applied perspectives. Dispersal can have clear evolutionary and ecological consequences, but for nonnative insect pests, dispersal capacity can also help to explain invasion success. Vespula germanica is a social wasp that, in the last century, has successfully invaded several regions of the world, showing one of the highest spread rates reported for a nonnative insect. In contrast with nonsocial wasps, in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Data on gynes were obtained from Masciocchi et al. (). Flight distance data were fitted to the exponential function: probability = scale (growth rate × flight distance) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on gynes were obtained from Masciocchi et al. (). Flight distance data were fitted to the exponential function: probability = scale (growth rate × flight distance) .…”
Section: Resultsmentioning
confidence: 99%
“…Although there is no established link between tethered flight mill patterns and movement in the field, our results suggest that dispersal in V. germanica could be gyne‐biased, with a higher proportion of drones remaining in the vicinity of the parental nest (66% of drones fly less than 500 m), whereas gynes have the capacity of flying larger distances (60% of gynes fly more than 2 500 m), but still a proportion of the gynes fly as little as drones. Although tethered flight assays are a simplification of what occurs in natural environments, it is an accepted method to compare movement potential of flying animals (Brodschneider et al., ; Bruzzone et al., ; Tosi et al., ; Masciocchi et al., ), especially useful in species where quantifying flight patterns in the field is difficult. It is also important to note that our tethered flight‐mill studies are limited in the sense that flight potential was measured in the absence of potentially relevant information during the process of mate location, such as visual and olfactory cues, and abiotic factors such as natural light and wind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With gynes not having a selective behavior toward potential mates, a mechanism to increase outbreeding, regulated by drones, would make sense. It has been recently suggested that dispersal in V. germanica is gyne-biased, while gynes have the potential of flying relatively large distances, drones fly relatively little, which implies remaining in the vicinity of the parental nest, where kin density is high 8,39 . This would suggest that, if no additional mechanism for increasing aggregation heterogeneity was in place, the risk of drone aggregations being conformed by a relatively high proportion of nestmates, would be high.…”
Section: Discussionmentioning
confidence: 99%
“…Foraging is the most complex behavior of social wasps (Richter 2000) with a behavioral sequence of travel, searching, preying, loading, return, and discharging the load in the nest (Brügger et al 2019a). However, we believe that flight capacity of social wasps should be studied to define their foraging area (Mandal et al 2017;Masciocchi et al 2018) and to determine the predatory potential of these insects (Dejean 2017). Here we report on investigations of the flight area and return capacity of P. lanio lanio workers in Seropédica, Rio de Janeiro State, Brazil.…”
Section: Introductionmentioning
confidence: 99%